2009
DOI: 10.1111/j.1447-0756.2008.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high‐dose methotrexate therapy on the primordial follicles of the mouse ovary

Abstract: Our study shows that high-dose MTX causes damage to the primordial follicles of the ovaries of mice. This result may be important because young women taking high-dose MTX may suffer diminished reproductive performance and premature cessation of menses in the years following therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…In the present study, evaluation of ovaries was carried out to examine as many follicles and corpus luteum as possible. Our results indicate MTX as an ovarian toxicant and correspond well with previous reports of disruption of follicles and ovarian cells by alkylating agents 85, 96, 118…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, evaluation of ovaries was carried out to examine as many follicles and corpus luteum as possible. Our results indicate MTX as an ovarian toxicant and correspond well with previous reports of disruption of follicles and ovarian cells by alkylating agents 85, 96, 118…”
Section: Discussionsupporting
confidence: 92%
“…Our results unambiguously substantiate the hypothesis that the fast proliferating cells in the female reproductive tissues are altered by MTX. The ability of alkylating agents to disrupt morphogenesis of ovary has previously been reported 20, 85. However, to the best of our knowledge this is the first report to mention the use of LCN and withdrawal of MTX treatment as mitigating factors.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…There is a profound lack of human studies looking into the relationship between cumulative MTX dose and ovarian reserve. Murine studies have identified damage to the primordial follicles following MTX therapy [4,18]. The underlying mechanism of MTX-related ovarian damage is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Wolff, Bern oder auch die moderneren Biologikatherapien haben eher keinen negativen Einfluss, wie sich v. a. im Tiermodell gezeigt hat [5,6,7].…”
Section: Cyclophosphamidtherapieunclassified